Digital Green Economy Module to Foster Green Behavior in Grade X Students - Ainiyah, Maf Ulatul; Subroto, Waspodo Tjipto; Hakim, Luqman (IJE : Interdisciplinary Journal of Education, 2025)
Global environmental crises, driven by unsustainable economic practices, highlight the urgent need for a transition toward a green economy. Education plays a crucial role in this transition by fostering green behavior among the younger generation. However, a significant gap exists in the availability of specific teaching materials that integrate green economy concepts into the economics curriculum within a local context. This study addresses that gap by developing and testing a digital-based Green Economy Module for 10th-grade students in an environmentally vulnerable region. Employing a Research and Development (R&D) approach using the ADDIE model, this study created a learning module that underwent rigorous validation by content, language, and graphics experts, achieving a "very feasible" rating (94.40%). The module's practicality was confirmed with a "very practical" rating from students (97.2%). A quasi-experimental design was used to measure effectiveness. The results showed that the module is significantly more effective than conventional methods in enhancing students' cognitive understanding. Furthermore, the module was found to be effective in shaping students' green behavior, raising the overall average from 59.6% to 70.6%. The findings confirm that a digital-based Green Economy Module, when developed with a contextual approach, can be an innovative and effective solution for improving student understanding and fostering sustainable behavior.